2012
DOI: 10.1039/c1ja10275c
|View full text |Cite
|
Sign up to set email alerts
|

Preconcentration of ultra-trace germanium in water samples with nano-sized TiO2colloid and determination by GFAAS with colloid sampling

Abstract: A method for preconcentration and determination of ultra-trace germanium is presented in this work. Germanium (Ge(IV) in this work) in the water samples was preconcentrated by applying nano-sized TiO 2 colloid as adsorbent. When the pH values of solution were 6.0-8.0, the adsorption efficiency of nano-sized TiO 2 colloid for germanium reached 97.0 $ 99.0% in a short time. After centrifugation, the sediment which contained the concentrated Ge(IV) was inverted to colloid by adding HNO 3 of certain concentration.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…[12][13][14][15][16] Compared with nanosized TiO 2 powder, the colloids possess the advantage of easily changing from the solid phase to the colloid phase aer adsorption and centrifugation. The required input of colloids is low because of their high adsorption capacity, and an autosampler can be used because the viscosity of the resulting solution is close to that of the aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] Compared with nanosized TiO 2 powder, the colloids possess the advantage of easily changing from the solid phase to the colloid phase aer adsorption and centrifugation. The required input of colloids is low because of their high adsorption capacity, and an autosampler can be used because the viscosity of the resulting solution is close to that of the aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that TiO 2 NPs colloid could preconcentrate the ultratrace germanium in water samples because of its great adsorption property. 6 Basically, the adsorption property of a photocatalyst would actually in°uence the enablement and conduct of the photocatalysis reaction. Thus, it is valuable to prepare well dispersed and stable TiO 2 colloid.…”
Section: Introductionmentioning
confidence: 99%
“…The tolerance limits (w/w) less than ±3% change in the per centage uptake of germanium ions was taken as being free from the interference. The experimental results indicated that alkaline and earth-alkaline metals, Zn(II), Cd(II), Mn(II), Ni(II), Co(II), Al(III), Ga(III), In(III), Bi(III), Ti(IV), Zr(IV), Hf(IV), Sn(IV) and Pb(IV) as well as anions had no significant effect on the separation and determination of Ge(IV) under the recommended conditions, and the most serious interference arose from Cu(II) and Fe(III) ( [2,3,27,30]. The now described results also clearly indicate that the proposed sorbents can be applied for the column preconcentration/enrichment of germanium in the presence of high background matrix.…”
Section: Effect Of the Interfering Speciesmentioning
confidence: 99%
“…It is rather rare and is found in nature dispersed in ore deposits or being dissolved in trace quanties, mainly as soluble germanate anions and methylgermanium species [2,3]. The concentration of germanium and its easy determination on the trace and ultra-trace levels is of importance and has been pursued for many years [1,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation